Strategies to Improve Drug Strength in Nasal Preparations for Brain Delivery of Low Aqueous Solubility Drugs - Patrícia C. Pires; Márcio Rodrigues; Gilberto Alves; Adriana O. Santos (MDPI AG, 2022)
Intranasal administration is a promising route for brain drug delivery. However, it can be difficult to formulate drugs that have low water solubility into high strength intranasal solutions. Hence, the purpose of this work was to review the strategies that have been used to increase drug strength in intranasal liquid formulations. Three main groups of strategies are: the use of solubilizers (change in pH, complexation and the use cosolvents/surfactants); incorporation of the drugs into a carrier nanosystem; modifications of the molecules themselves (use of salts or hydrophilic prodrugs). The use of high amounts of cosolvents and/or surfactants and pH decrease below 4 usually lead to local adverse effects, such as nasal and upper respiratory tract irritation. Cyclodextrins and (many) different carrier nanosystems, on the other hand, could be safer for intranasal administration at reasonably high concentrations, depending on selected excipients and their dose. While added attributes such as enhanced permeation, sustained delivery, or increased direct brain transport could be achieved, a great effort of optimization will be required. On the other hand, hydrophilic prodrugs, whether co-administered with a converting enzyme or not, can be used at very high concentrations, and have resulted in a fast prodrug to parent drug conversion and led to high brain drug levels. Nevertheless, the choice of which strategy to use will always depend on the characteristics of the drug and must be a case-by-case approach.